Simulasi Numerik dan Validasi Experimental Distribusi Aliiran Udara di Dalam Cooling Tower - Prasetyo, Bambang Teguh (MESIN, 2007)
Numerical Simulation and Experimental Validation ofAir Flow Distribution in CoolingTower. Numerical simulation and experimental validation of air flow distribution in induced draftCooling Tower (CT) has been done. Numerical simulation was done by using Computational FluidDynamics (CFD) software, while measurement was conducted by using a testfacility exist in BTMPBPPTThis studyis aimedto assist thepreliminary analysis predicting thatone ofcause a higherofmakeup waterconsumption in CTis mal-distribution ofair stream in CT. The results ofnumerical simulationand testing shows that tendency of mal-distribution of air stream is true happened. But to ensure thatwhether this mal-distribution ofairflow mentioned as the root cause ofheight consumemake waterstillrequireto be proved after theCTprovided withhomogeniser ofair stream.